High-Grade Osteosarcoma Arising in Monostotic Fibrous Dysplasia of the Skull: A Rare Case without Prior Radiation Exposure - Iftikhar, Shehla; Shafiq, Sunnia; Kanwal, Shagufta; Manzoor, Hina; Ahmad, Hafiz Khush Naseeb (http://dharmais.co.id/, 2026)
Introduction: Osteosarcoma is an uncommon, aggressive bone tumor that seldom develops in the skull, particularly when fibrous dysplasia is present, and there has been no previous radiation exposure. In fibrous dysplasia, malignant transformation is usually associated with radiation therapy, McCune-Albright syndrome, or polyostotic illness. Improving patient outcomes requires early diagnosis and action.Case Report: We present a 35-year-old male who developed progressive right mandibular edema and pain. A well-defined lesion with a combination of sclerotic and osteolytic features was seen on imaging. A biopsy revealed fibrous dysplasia and high-grade osteosarcoma coexisting. The patient received adjuvant chemotherapy after surgical resection. The histopathological analysis confirmed the diagnosis, and the surgical process was uneventful. A favorable prognosis was suggested by follow-up evaluations that revealed neither metastases nor local recurrence.Conclusion: This case was reported to highlight the possibility of high-grade osteosarcoma arising from monostotic fibrous dysplasia in the skull, even in the absence of radiation exposure or systemic risk factors, an exceedingly rare but clinically significant occurrence.